Reaksi Investor Juventus terhadap Event Transfer Cristiano Ronaldo dan Matthijs De Ligt - Ismail, Andy; Arianto, Pipit (Keizai, 2021)
This research was conducted because previous studies relating to player transfers and their effects on stock returns are still rarely examined, whereas in the ball industry many soccer clubs are listed. This research focuses on the transfer of Cristiano Ronaldo and Matthijs De Ligt conducted by Juventus Football Club and aims to examine the transfer event of Cristiano Ronaldo and Matthijs De Ligt conducted by Juventus Football Club influencing the reaction of Juventus investors viewed abnormal returns. The time period used at the event starts from July to September 2018 at the transfer event of Cristiano Ronaldo and starts from July to September 2019 at the transfer event of Matthijs De Ligt. The abnormal return calculation method used in this study is the CAPM (Capital Asset Pricing Model). From the results of this study, it was found that the transfer event of Cristiano Ronaldo and Matthijs De Ligt conducted by Juventus Football Club did not affect investor reaction.